LEGAL MEASURES IN THAILAND PERTAINING TO CONTRACT FARMING REGARDING LIABILITY FOR THE PRODUCTION OF AGRICULTURAL CROPS WITH CERTIFIED QUALITY AND SAFETY STANDARDS - Nueangnong, Visitsak; Kulvitid, Kulpranee; Tubauttanon, Pratheep; Ployjan, Omjate (Rangsit Journal of Law and Society, 2024)
Agriculture crops is vital to Thailand’s food supply, with many produced under the contract farming system established during the 6th National Economic and Social Development Plan (1987-1991). These crops typically meet quality and safety standards before reaching consumers. However, if consumers cause harm to their health and body by consuming contaminated agricultural products, the producer must be held accountable if agricultural products cause harm to consumers. Nevertheless, the insecurity of these foods makes it impossible to determine who is directly accountable to the consumer. Additionally, consumers face unfair treatment in legal proceedings and lack appropriate remedies and protections against these infringements. This research proposes establishing a central standard for measuring product quality by setting a common standard that all food business operators should use as the same standard to enforce uniformly across all food businesses. It also recommends creating institutions for oversight and requiring food businesses in the contract farming system to register, ensuring a proper database for future consumer protection. The Ministry of Agriculture crops and Cooperatives should supervise appropriate institutions or organizations, and this information should be used to determine accountable persons. As for the problem of not receiving fair compensation for damages to consumers, the researcher proposes adding the word “Product quality” to the definition of the word “Unsafe products” in Section 4 of the Unsafe Goods Damage Liability Law, B.E. 2551 (2008) to cover the interpretation of product defects as well as product quality; the word “Within a reasonable time” in Section 4 (3) to provide clarity in enforcing the law and being fair to both the injured party and the seller. Furthermore, it should be agreed that a fund should be established to assist consumers damaged by the consumption of unsafe products under the Unsafe Goods Damage Liability Law, B.E. 2551 (2008), creating a more comprehensive system of accountability and support for affected individuals.